Terpenoid Emissions of Two Mediterranean Woody Species in Response to Drought Stress - Haberstroh, Simon; Kreuzwieser, Jürgen; Lobo-do-Vale, Raquel; Caldeira, Maria C.; Dubbert, Maren; Werner, Christiane (Frontiers in Plant Science, 2018)
Drought is a major environmental constrain affecting plant performance and survival, particularly in Mediterranean ecosystems. Terpenoids may play a protective role under these conditions, however observations of drought effects on plant terpenoid emissions are controversial ranging from decreased emissions to unaffected or increased release of terpenoids. In the present study we investigated terpenoid emissions of cork oak (Quercus suber) and gum rockrose (Cistus ladanifer) in response to summer drought stress in 2017. Pre-dawn leaf water potential (ΨPD) decreased from -0.64 to -1.72 MPa in Q. suber and from -1.69 to -4.05 MPa in C. ladanifer, indicating a transition from mild to severe drought along summer. Total terpenoid emissions decreased with drought, but differed significantly between species (p<0.001) and in response to ΨPD, air temperature and assimilation rates. Cistus ladanifer emitted a large variety of >75 compounds comprising monoterpenes, sesquiterpenes and even diterpenes, which strongly decreased from 1.37 ± 0.23 µg g-1 h-1 to 0.40 ± 0.08 µg g-1 h-1 (p<0.001) in response to drought. Total emission rates were positively correlated to air temperature (p<0.001). Cistus ladanifer behaviour points towards terpenoid leaf storage depletion and reduced substrate availability for terpenoid synthesis with increasing drought, most likely accelerated by high air temperatures. Quercus suber emitted mainly monoterpenes and emissions declined significantly from June (0.50 ± 0.08 µg g-1 h-1) to August (0.29 ± 0.02 µg g-1 h-1) (p<0.01). Emission rates were weakly correlated with net assimilation rates (R² = 0.19, p<0.001), but did not respond strongly to ΨPD and air temperature. Early onset of drought in 2017 most likely reduced plant metabolism in Q. suber, resulting in diminished, but stable terpenoid fluxes. Calculation of standard emission factors (at 30 °C) revealed contrasting emission patterns of decreasing, unaffected, or increasing fluxes of single terpenoid compounds. Unaffected or drought-enhanced emissions of compounds such as α-pinene, camphene or manoyl oxide may point towards a specific role of these terpenoids in abiotic stress adaptation. In conclusion, these results suggest a strong negative, but species- and compound-specific effect of severe drought on terpenoid fluxes in Mediterranean ecosystems.